장애와 AI: 뉴스기사 토픽모델 분석 - 박련훤(Ryeon Hwon Park); 박윤현(Yun Hyun Pack); 정가윤(Ka Youn Chung) (가정과삶의질연구, 2024)
이 연구의 목적은 장애와 AI를 포함하고 있는 뉴스 기사에서 다루는 단어들을 알아보고, AI 기술은 장애 혹은 장애인 요인과 관련하여어떻게 나타나고 있는지 살펴보고자 한다. 이를 위하여 2010년 1월 1일부터 2024년 4월 30일까지 장애와 AI를 포함하고 있는 뉴스기사 14,327건을 한국언론진흥재단의 빅카인즈를 활용하여 수집하고, 토픽모델링을 활용하여 분석하였다. 장애와 AI 관련 뉴스 기사의경향성을 알아보기 위하여 연도별로 장애와 AI를 포함하고 있는 뉴스 기사의 발행 건수의 변화를 살펴보았으며, 뉴스 기사의 문서-단어행렬(document-term matrix)에서 상위 출현 빈도 키워드 25개 단어를 살펴보았다. 또한, 상위 출현 빈도 키워드 50개 단어를 워드 클라우드를 활용하여 시각적으로 표현하였고 장애와 AI를 중심으로 연관이 있는 단어를 추출하여 대표 단어와 연관 단어 간의 관계를 살펴보았다. 그리고 토픽모델링을 실시하여 장애와 AI를 포함하고 있는 뉴스 기사의 토픽을 살펴보았다. 분석 결과 첫째, 장애와 AI를 포함하고있는 뉴스 기사는 지속적인 증가 추세를 보이고 있는 것으로 나타났다. 둘째, 장애와 AI를 포함하고 있는 뉴스 기사의 핵심 단어는 장애와 관련된 ‘장애’, ‘지원’, ‘사회’, ‘활용’ 등이었으며, AI와 관련된 ‘AI’, ‘서비스’, ‘디지털’, ‘데이터’, ‘로봇’ 등이 자주 등장하는 단어로 나타났다. 셋째, 장애와 AI 관련 뉴스 기사의 토픽 수는 열여섯 개로 나타났고 크게 네 가지의 대주제로 구분할 수 있었다. 네 가지 대주제는보편적 지원을 통한 장애인의 AI 활용, 삶의 질 향상을 위한 장애인의 AI 활용, AI를 통한 제한적인 장애인 삶의 범위 확장, 장애인의AI 활용에 대한 미래 방향이었다. 이러한 결과는 지금까지 다루지 않았던 장애인의 AI 활용 분야와 AI 지원의 필요성을 사회 맥락적으로구체화하였으며, 앞으로 장애인의 AI 활용에 대한 지원 방향성을 살펴보았다는 점에서 중요한 의의를 찾을 수 있다. This study investigates to find out the words covered in news articles containing disability and AI, and to examine how AI technology appears in relation to disability or disability factors. We analyzed 14,327 news articles including disability and AI using Topic Modeling from January 1st, 2010 to April 30th, 2024. and news articles containing disability and AI were collected using the Big Kines of the Korea Press Promotion Foundation. In order to find out the trend of news articles related to disability and AI, we looked at the changes in the number of news articles published containing disability and AI by year, and looked at 25 words of the top frequency of appearance keywords in the document-term matrix of news articles. In addition, 50 words of the top frequency of appearance keywords were visually expressed using the word cloud, and the relationship between representative words and related words was examined by extracting words related to disability and AI. And by conducting topic modeling, we looked at the topics of news articles containing disability and AI. The analysis yielded the following results. first, the number of news articles including disability and AI gradually increased. Second, the key words of news articles containing disability and AI were ‘disability’, ‘support’, ‘society’, and ‘utilization’ related to disability, and ‘AI’, ‘service’, ‘digital’, ‘data’, and ‘robot’ related to AI appeared frequently. Third, the number of topics related to disability and AI appeared as 16 and could be largely classified into four main topics. These four main topics were AI uses for the disabled through universal support, AI uses for the quality of life improvement, AI uses for expansion of the disabled’s limited scope of life, and future directions for AI uses for the disabled. These results are significant in that they examine the field of AI use for the disabled and the need for AI support, which have not been covered so far, in the social context, and look at the direction of support for the use of AI for the disabled in the future. KCI Citation Count: 0